Dicoumarol sensitizes hepatocellular carcinoma cells to ferroptosis induced by imidazole ketone erastin - Yang, Ziwei; Han, Tixin; Yang, Ruibin; Zhang, Yinuo; Qin, Yifei; Hou, Jialu; Huo, Fei; Feng, Zhuan; Ding, Yaxin; Yang, Jiali; Zhou, Gang; Wang, Shijie; et al. (Frontiers in Immunology, 2025)
IntroductionFerroptosis, an iron-dependent form of regulated cell death, is characterized by the lethal accumulation of lipid peroxides on cellular membranes. It not only inhibits tumor growth but also enhances immunotherapy responses and overcomes drug resistance in cancer therapy. The inhibition of the cystine-glutamate antiporter, system Xc–, induces ferroptosis. Imidazole ketone erastin (IKE), an inhibitor of the system Xc– functional subunit solute carrier family 7 member 11 (SLC7A11), is an effective and metabolically stable inducer of ferroptosis with potential in vivo applications. However, tumor cells exhibited differential sensitivity to IKE-induced ferroptosis. The intrinsic factors determining sensitivity to IKE-induced ferroptosis remain to be explored to improve its efficacy.MethodsBulk RNA-sequencing data from hepatocellular carcinoma (HCC) and normal liver tissues were collected from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) databases. Differentially expressed genes were identified and intersected with the ferroptosis-related genes (FRGs) listed in the FerrDb database, yielding the identification of 13 distinct FRGs.ResultsA ferroptosis signature index model (Risk Score) was developed to predict HCC prognosis. And SLC7A11 and NAD(P)H quinone dehydrogenase 1 (NQO1) were identified as candidate FRGs indicating poor prognosis of HCC. Dicoumarol (DIC), an inhibitor of NQO1, was subsequently employed to assess its sensitizing effects on IKE in HCC treatment. In HCC cell lines and the subcutaneous xenograft model, the combined suppression of SLC7A11 and NQO1 significantly enhanced the inhibitory effect on tumor growth by inducing ferroptosis.DiscussionIn conclusion, our findings demonstrate that DIC sensitized HCC cells to IKE-induced ferroptosis in HCC. Moreover, the identification of potential drugs that enhance the susceptibility of HCC cells to ferroptosis could provide novel therapeutic strategies for the treatment of HCC.